Inhibitory synaptic transmission is impaired at higher extracellular Ca2+ concentrations in Scn1a +/− mouse model of Dravet syndrome - Kouya Uchino (Nature Portfolio, 2021)
Abstract Dravet syndrome (DS) is an intractable form of childhood epilepsy that occurs in infancy. More than 80% of all patients have a heterozygous abnormality in the SCN1A gene, which encodes a subunit of Na+ channels in the brain. However, the detailed pathogenesis of DS remains unclear. This study investigated the synaptic pathogenesis of this disease in terms of excitatory/inhibitory balance using a mouse model of DS. We show that excitatory postsynaptic currents were similar between Scn1a knock-in neurons (Scn1a +/− neurons) and wild-type neurons, but inhibitory postsynaptic currents were significantly lower in Scn1a +/− neurons. Moreover, both the vesicular release probability and the number of inhibitory synapses were significantly lower in Scn1a +/− neurons compared with wild-type neurons. There was no proportional increase in inhibitory postsynaptic current amplitude in response to increased extracellular Ca2+ concentrations. Our study revealed that the number of inhibitory synapses is significantly reduced in Scn1a +/− neurons, while the sensitivity of inhibitory synapses to extracellular Ca2+ concentrations is markedly increased. These data suggest that Ca2+ tethering in inhibitory nerve terminals may be disturbed following the synaptic burst, likely leading to epileptic symptoms.